Duelo migratorio y resiliencia en personas adultas en situación de movilidad humana que residen en la ciudad de Loja, periodo 2022-2023 - Elizalde Guerrero., Jenny Susana (2023)
The objective of this research was to determine the types of migratory mourning and the level of resilience in adults in a situation of human mobility residing in Loja city. The methodology used was quantitative, descriptive in scope, non-experimental and crosssectional design; incidental sampling by convenience was used, the sample consisted of 60 participants, 46 women and 14 men, aged between 19 and 82 years; the instruments used to obtain data were: sociodemographic interview, the Kayak Test for migratory grief, and the Resilience Scale (ER-14) to measure the degree of resilience; Excel and SPSS Statistics version 25 were used for the statistical analysis of the data. The results show that most of the study sample has an adaptive mourning in the seven dimensions of migratory mourning evaluated, however, there is a considerable percentage of maladaptive and pathological mourning in the culture, land, social status and physical risks dimensions; regarding the degrees of resilience, these are mostly located in a normal, high and very high level, while a minimum percentage have a low level of resilience. Finally, considering the population with maladaptive mourning and low level of resilience, a psychological prevention plan was designed to help solve the emotional needs present in this area